2014
DOI: 10.1177/1362168814541722
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teacher beliefs and classroom practices through reflective practice: A case study

Abstract: This article presents a case study that explored and reflected on the relationship between the stated beliefs and observed classroom practices of one second language reading teacher. The findings of this study revealed that this particular teacher holds complex beliefs about teaching reading that were evident to some extent in many of his classroom practices. Additionally, this study found that by articulating and reflecting on his beliefs, the teacher became more aware of the meaning and impact of these belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 18 publications
8
87
0
8
Order By: Relevance
“…In a study by Farrell and Ives (2015), the results showed that since teachers were developing in the first year of teaching, some observed practices were not expressed in the teachers' beliefs.…”
Section: Discussionmentioning
confidence: 96%
“…In a study by Farrell and Ives (2015), the results showed that since teachers were developing in the first year of teaching, some observed practices were not expressed in the teachers' beliefs.…”
Section: Discussionmentioning
confidence: 96%
“…The method was chosen in accordance to Farrell and Ives's (2015) contention that the case study method helps address the lacunae in the literature on second language teachers' beliefs and practices by gathering rich data using multiple sources of data and techniques for collection and analysis (e.g., questionnaire and classroom observation).…”
Section: Methodsologymentioning
confidence: 99%
“…En este contexto, se ha planteado que las creencias pueden ser transformadas a través de su cuestionamiento constante (Farrell e Ives, 2015). Este planteamiento involucra explorar y reconocer la naturaleza de las propias prácticas pedagógicas, proceso que se relaciona con la reflexión en y sobre la acción.…”
Section: Marco De Referencia Creenciasunclassified